Opto-mechanical programming of micro-scale information on transparent multilayer shape memory film. (14th February 2018) - Li, Zhenpeng; Black, Taylor; Rahman, Md Arifur; Feng, Jingxing; Olah, Andrew; Baer, Eric
Abstract: Micro-scale surface shape memory effects were investigated on multilayer films that were produced with alternating layers of PVAc and PU. Two different types of micro-scale patterns, including a sharp microprismatic pattern and a smooth microlens pattern, were embossed on the surface of the PVAc/PU multilayer films by a PDMS replica mold using the soft lithography method. The microprismatic pattern as a permanent surface structure on the intrinsically transparent multilayer films renders the films opaque and the microlens surface pattern endows the clear films with focusing properties. The micro-structured surface is programmed by compression and recovery to switch the corresponding optical property of the film. Based on this switchable optical property, the patterned PVAc/PU multilayer film can be employed as an anti-counterfeiting feature in packaging. In this paper, the shape memory effect of the multilayered film was found to be dependent on the composition of the PVAc relative to the PU layers. In addition, the shape memory effect of the layered PVAc/PU films was enhanced compared to the PVAc control film. The recovery mechanism of the shape memory films was interpreted using Burgers viscoelastic model. The effects of the compression pressure, recovery temperature and the geometry of the patterns on the micro-scale shape memory behavior of the PVAc/PU multilayer films were also investigated. Graphical abstract: Image 1 Highlights: Transparent multilayer shape memory films with alternating PVAc and PU layers are produced by forced assembly co-extrusion. Micro-scale patterns are programmed on the surface of PVAc/PU multilayer films to switch the optical property. Recovery of surface pattern is affected by composition, compression pressure, recovery temperature and pattern geometry. Burgers viscoelastic model is used to interpret the recovery mechanism of the PVAc/PU multilayer films.